"x^2p + y^2q = z^2\\\\\n\n\\textsf{The lagrange auxiliary equation is}\\\\\n\n\\frac{\\mathrm{d}x}{x^2} = \\frac{\\mathrm{d}y}{y^2} = \\frac{\\mathrm{d}z}{z^2} \\\\\n\n\n\\frac{\\mathrm{d}x}{x^2} + \\frac{\\mathrm{d}y}{y^2} - 2\\frac{\\mathrm{d}z}{z^2} = 0\\\\\n\n\n\\textsf{Choosing}\\,\\,\\left(\\frac{1}{x^2}, \\frac{1}{y^2}, -2\\frac{1}{z^2}\\right) \\,\\,\\textsf{as multpliers.}\\\\\n\n\\int\\frac{\\mathrm{d}x}{x^2} + \\int\\frac{\\mathrm{d}y}{y^2} - 2\\int\\frac{\\mathrm{d}z}{z^2} = 0\\\\\n\n-\\frac{1}{x} - \\frac{1}{y} + 2\\frac{1}{z} = C\\\\\n\n\\frac{1}{x} + \\frac{1}{y} - 2\\frac{1}{z} = C\\\\\n\nyz + xz - 2xy = Cxyz\\\\\n\n\n\n\\textsf{Let}\\,z\\,\\textsf{be constant}.\\\\\n\n\\textsf{It implies}\\,\\, \\frac{\\mathrm{d}x}{x^2} - \\frac{\\mathrm{d}y}{y^2} = 0.\\\\\n\n\\int\\frac{\\mathrm{d}x}{x^2} - \\int\\frac{\\mathrm{d}y}{y^2} = 0\\\\\n\n-\\frac{1}{x} = -\\frac{1}{y} + \\phi(z), \\frac{1}{x} - \\frac{1}{y} = -\\phi(z)\\\\\n\ny - x = \\phi(z)xy\\\\\n\n\\frac{1}{x} - \\frac{1}{y} = -\\phi(z)\\\\\n\n-\\frac{1}{x^2} + \\frac{1}{y^2}\\frac{\\mathrm{d}y}{\\mathrm{d}x} = \\frac{\\mathrm{d}(\\phi(z))}{\\mathrm{d}z}\\cdot\\frac{\\mathrm{d}z}{\\mathrm{d}x}\\\\\n\n\\frac{\\mathrm{d}x}{x^2} - \\frac{\\mathrm{d}y}{y^2} = -\\frac{\\mathrm{d}(\\phi(z))}{\\mathrm{d}z}\\cdot\\mathrm{d}z \\\\\n\n\\frac{\\mathrm{d}x}{x^2} - \\frac{\\mathrm{d}y}{y^2} = 0\\cdot\\mathrm{d}z \\\\\n\n\n\\frac{\\mathrm{d}(\\phi(z))}{\\mathrm{d}z} = 0\\\\\n\n\\mathrm{d}(\\phi(z)) = 0\\cdot\\mathrm{d}z \\\\\n\n\\int\\mathrm{d}(\\phi(z)) = \\int 0 \\cdot\\mathrm{d}z\\\\\n\n\\displaystyle\\therefore \\phi(z) = C\\\\\n\n y - x = Cxy\\\\\n \\phi\\left(\\frac{1}{x} - \\frac{1}{y}, \\,\\frac{1}{x} + \\frac{1}{y} - \\frac{2}{z}\\right) = 0,\\,\\,\\textsf{is the solution to the PDE}"
Comments
Leave a comment